PENGATURAN HAK KEKAYAAN INTELEKTUAL DALAM MASYARAKAT KOMUNAL DI INDONESIA - Robiatul Adawiyah; Rumawi Rumawi (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2021)
The Communal Intellectual Property of Indonesia is susceptible to recognition, theft, and piracy of other countries because Indonesia is still not a sovereign guarding culture. Regulations of Unesco, sui generis system from Convention on Biological Diversity (CBD) and regulation of Malaysia year 2005 AKTA 645 about national heritage it is tangible proof that cultures must have a specific binding arrangement to protect for it. This research purpose to know the setting of intellectual property rights in comunal societies Indonesia by normative legal research methods. The findings that there is weaknesses in protecting communal societies set on a few rules that is copyrigts law, patent law, and merk law so that gives rise to ambience. The legal protection of communal rights against intellectual property requires a special law containing definitions and ling space and the existance of a special agency that regulates its application mechanisms.